Students’ Academic Resilience: A Descriptive Study - Rachmawati, Indriyana; Astuti, Budi; Kurniasari, Mitta (citeus, 2025)
College students are confronted with evolving social roles and novel psychological conditions that can influence their academic resilience. Academic resilience represents a crucial and indispensable capacity of students to navigate various academic and career challenges in the future. This phenomenon occurs when academic resilience enables students to transform feelings of helplessness into a source of strength, empowering them to confront academic adversity in college. This study aims to elucidate the academic resilience profile of students in Yogyakarta and Malang, Indonesia. The research was conducted using quantitative methods with a survey research design. The research subjects were students in the cities of Yogyakarta and Malang, with a total of 412 students who were willing to be involved in the study. Purposive sampling was used as the sampling technique, and an academic resilience scale was employed to measure the level of academic resilience of students. The garnered research data were analyzed using descriptive statistics to obtain a profile of student academic resilience. The results indicated that there was no significant difference in academic resilience between students in Yogyakarta and Malang, Indonesia. Both groups of students exhibited good personal qualities but lacked the ability to build a sense of physical and emotional security.